Implementing Roleplay Strategy To Help Trainees' Speaking Ability At English Language Teaching Assistance (ELTA) Maluku and North Maluku (MMU) Program - Renata C. G. V. Nikijuluw (MATAI: International Journal of Language Education, 2022)
The article focused on the Roleplay strategy and the way to improve trainees' speaking ability. The subject of this research is the ELTA MMU trainees, and the materials used were taken from the concept of Role Play. This research consists of two cycles, with five meetings for the first cycle and three meetings for the second cycle, based on the schedule designed by the researcher. The researcher used oral tests to collect the data, and a questionnaire was used to gain the trainees' responses to Role Play. The data collected from this research shows that ELTA trainees' speaking ability is improved through Role Play. The trainees give positive opinions and responses during the use of Role Play. Based on the data, the researcher concluded that the element of speaking that has more progress for trainees' speaking improvement is comprehensive. The data shows that 9 to 10 trainees scored 3 in the first cycle, but in the second cycle, 8 to 15 participants successfully achieved a score of 4. From the result, it can be proved that the use of Role Play is successful in improving trainees' speaking ability.